Advancing Reliability of Membrane-Based Corrosion and Environmental Sensor in Simulated Natural Gas. (19th June 2018) - Duffy, Timothy; Hall, Derek M.; Ziomek-Moroz, Margaret; Lvov, Serguei N.
Abstract : A significant progress was made on developing membrane-based advanced electrochemical sensors (AESs) to improve their consistency, cost, and measurement quality by means of experimentation and finite element analysis. Consistency of the AESs were improved by better characterization of the cell geometry and localized thermocouple installation. Experimental artefacts were reduced by connecting the working and reference electrodes with 50 nF capacitors. Finite element analysis shows that the AESs should incorporate thin, long electrodes with small separations in contact with a thicker membrane to improve measurement quality.